2017
DOI: 10.1093/treephys/tpx146
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phosphorus nutrition, allocation and growth of young beech (Fagus sylvatica L.) trees in P-rich and P-poor forest soil

Abstract: To investigate how long-lived forest trees cope with low soil phosphorus (P) availabilities, we characterized P nutrition of beech (Fagus sylvatica, L.) in soils from P-rich and P-poor beech forests throughout an annual growth cycle. Young trees were excavated with intact soil cores in mono-specific beech forests, kept under common garden conditions, and used for 33P labeling, analyses of P uptake, P content and biomass during five phenological stages (dormancy in winter, bud swelling in early spring, mature l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…The extent to which plants can alter their biomass allocation in response to P limitation is key to their growth response. Observed responses include increased root biomass (Keith et al ., ), faster root turnover (Laliberté et al ., ), and seasonal decoupling of growth and P acquisition (Zavišić & Polle, ). An ecosystem‐level C budget study showed that plants can respond to reduced P availability via a shift in internal C allocation, with little change in canopy biomass and total productivity but an enhanced root growth (Keith et al ., ).…”
Section: Carbon Allocationmentioning
confidence: 99%
See 3 more Smart Citations
“…The extent to which plants can alter their biomass allocation in response to P limitation is key to their growth response. Observed responses include increased root biomass (Keith et al ., ), faster root turnover (Laliberté et al ., ), and seasonal decoupling of growth and P acquisition (Zavišić & Polle, ). An ecosystem‐level C budget study showed that plants can respond to reduced P availability via a shift in internal C allocation, with little change in canopy biomass and total productivity but an enhanced root growth (Keith et al ., ).…”
Section: Carbon Allocationmentioning
confidence: 99%
“…More efficient internal P recycling is another strategy for plants to respond to external P limitation (Adams, ; Zavišić & Polle, ). As plants age, a larger proportion of the P utilised in new growth is obtained from remobilisation rather than uptake (Jin et al ., ; Lang et al ., ).…”
Section: Plant Internal P Redistributionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Spohn et al . ; Zavišić & Polle ). P i bound to Fe and/or Al oxy(hydr)oxides in the soil (Prietzel et al .…”
Section: Aspects Of Pi Acquisition By Trees In the Fieldmentioning
confidence: 99%